JITU TRICKS FAST GRADUATION (CONCEPT-EMPIRIC ANALYSIS OF STUDENT STUDY PROBLEMS) - I Nengah Suastika (Universitas Pendidikan Ganesha, 2020)
Graduation quickly and carrying diplomas are the main goals that must be achieved by all students, in addition to knowledge skills, attitudes and skills as intellectuals. However, it is not uncommon for students to experience failures in completing their studies due to various factors. Studies conducted by several universities in Indonesia show that, on average, 4% do not get a diploma because they fail to complete their studies, 4% move universities to avoid dorp-out, and 20% experience problems in completing the study. The problems of this study can be caused due to various problems, both internal problems that exist within the student himself, as well as external problems that occur due to other causes outside the student. Internal factors usually involve students' academic abilities (academic scores), self-motivation, student performance, socio-demographics (age, gender, ethnicity, religion) and student social behavior. Meanwhile, the external factors concern the socio-economic conditions and family education, peer influence, social conditions of the community, departments, lecturers (teachers), the administration system, the university's academic culture, etc. These two factors influence each other in determining the successful completion of student studies